2010
DOI: 10.1007/s10900-010-9260-7
|View full text |Cite
|
Sign up to set email alerts
|

Health Assessment of the Arab American Community in Southwest Brooklyn

Abstract: Data on Arab American health is lacking nationwide. This survey of the Arab American community in southwest Brooklyn assessed perceptions of health status, needs, behaviors, and access to services. Bilingual interviewers administered a structured survey to community members in public gathering places. Of 353 surveyed, 43% were men and 57% women, most spoke Arabic and were Muslim, and most had moved to the U.S. after 1990. One quarter were unemployed. Over 50% reported household incomes below federal poverty le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 8 publications
2
34
1
Order By: Relevance
“…Arabs in these two studies reported lower SES, compared to Arab Americans nationally. A similar high rate of fair/poor SRH (26%) was reported among Arab immigrants in New York City (Sarsour et al, ). The sample was comprised mainly of young, recent Arab immigrants with low SES; their rate of fair/poor SRH was higher compared to foreign‐born adults (24%) and U.S.‐born adults (17%) in New York City.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Arabs in these two studies reported lower SES, compared to Arab Americans nationally. A similar high rate of fair/poor SRH (26%) was reported among Arab immigrants in New York City (Sarsour et al, ). The sample was comprised mainly of young, recent Arab immigrants with low SES; their rate of fair/poor SRH was higher compared to foreign‐born adults (24%) and U.S.‐born adults (17%) in New York City.…”
Section: Resultssupporting
confidence: 67%
“…Two studies were conducted on Arabs residing in Detroit, national samples were included in two studies, one study was conducted on Arab women in southern California, and one study was conducted in Brooklyn, New York. California, Detroit, and New York are the three areas with the greatest numbers of Arab immigrants (Abdulrahim & Baker, ; El‐Sayed & Galea, ; Sarsour et al, ). In the three studies conducted in Detroit and New York, Arab immigrants were of lower SES, were older in age, and had a greater percentage of first‐generation immigrants, compared to the samples of the other three studies in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key principle is the involvement of community members in the research process. CBPR approaches to survey studies and community health needs assessments are a promising strategy for accessing linguistically and culturally isolated communities [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that this population totals almost six million and is one of the fastest-growing immigrant groups in the United States [1,2,3,4,5], there have been few studies of smoking behavior among Arab American (ARA) men, who often have high rates of smoking. Indeed, the prevalence of cigarette smoking among men in the Middle East is very high (63% men, 10% women) [6,7] and once in the United States, the prevalence is approximately 20%–30% higher among ARA men than among the general U.S. adult male population.…”
Section: Introductionmentioning
confidence: 99%